2019
DOI: 10.1073/pnas.1812015116
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic dynamics of the abelian sandpile

Abstract: The abelian sandpile serves as a simple model system to study self-organized criticality, a phenomenon occurring in many important biological, physical and social processes. The identity element of the abelian group is a fractal composed of self-similar patches with periodic patterns, and the limit of this identity is subject of extensive collaborative research. Here, we analyze the evolution of the sandpile identity under harmonic fields of different orders. We show that this evolution corresponds to periodic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
(55 reference statements)
1
15
0
Order By: Relevance
“…It turns out that we can associate the "energy of the particle" with each world line such that total energy is conserved in these collisions. As it was recently shown (experimentally), quadratic patches may be thought of as a limit of many line-shaped patterns coming together during a relaxation [38].…”
Section: Line-shaped Patterns In the Literaturementioning
confidence: 87%
“…It turns out that we can associate the "energy of the particle" with each world line such that total energy is conserved in these collisions. As it was recently shown (experimentally), quadratic patches may be thought of as a limit of many line-shaped patterns coming together during a relaxation [38].…”
Section: Line-shaped Patterns In the Literaturementioning
confidence: 87%
“…For example, the order of the sandpile group on a 3 × 3 square domain is 2 11 7 2 , while the one on a 5 × 5 domain is 2 18 3 5 5 2 11 2 13 2 . Recently, we have shown that the sandpile group can be considered as a discretization of a |∂Γ|-dimensional torus, to which we refer to as the extended sandpile group [35]. We have then derived epimorphisms from the extended sandpile group on a given domain to the corresponding group on a subdomain.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…We have then derived epimorphisms from the extended sandpile group on a given domain to the corresponding group on a subdomain. On the level of the (usual) sandpile group, due to the discretization, this renormalization is however defined in the category of sets and in general only "approximates" group homeomorphism for sufficiently large domains [35]. Under which conditions these "approximations" can be lifted to true group homeomorphisms, if possible at all, is yet unknown.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Colors correspond to number of grains: white is 0, green is 1, blue is 2 and black is 3. Figure generated with the Interpile toolbox [57]. 12 Figure 2.3 Directed Percolation.…”
Section: A C K N O W L E D G M E N T Smentioning
confidence: 99%